2000
DOI: 10.2134/jeq2000.00472425002900060036x
|View full text |Cite
|
Sign up to set email alerts
|

Methane Oxidation at Low Temperatures in Soil Exposed to Landfill Gas

Abstract: Soil exposed to elevated methane concentrations can develop a high capacity for methane oxidation. Methane oxidation at high and low methane concentrations is performed by different types of methanotrops and therefore oxidation rates found at low temperatures at the atmospheric methane content cannot be extrapolated to soils exposed to high methane concentrations. Four sandy soils with different organic matter content (1–9% w/w) from two landfills in Denmark were investigated in batch experiments in the labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 0 publications
5
77
1
4
Order By: Relevance
“…The CH 4 oxidation rate increases with increasing soil organic content (Humer and Lechner, 2001;Christophersen et al, 2000;Visvanathan et al, 1999 soil incubation tests, Christophersen et al (2000) found that soils containing more organic matter more effectively mitigate CH 4 emissions through oxidation. They also found a relationship between the optimal soil moisture content and the organic matter content.…”
Section: Soil Organic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The CH 4 oxidation rate increases with increasing soil organic content (Humer and Lechner, 2001;Christophersen et al, 2000;Visvanathan et al, 1999 soil incubation tests, Christophersen et al (2000) found that soils containing more organic matter more effectively mitigate CH 4 emissions through oxidation. They also found a relationship between the optimal soil moisture content and the organic matter content.…”
Section: Soil Organic Contentmentioning
confidence: 99%
“…Four sandy soils from two landfills in Denmark were investigated in batch experiments by Christophersen et al (2000) to determine the effects of soil moisture on CH 4 oxidation. The results showed that the optimum moisture content range from 11 to 32% in all samples.…”
Section: Moisture Contentmentioning
confidence: 99%
“…It has been welldocumented, however, that temperature changes typically have little effect on overall methanotrophic activity in soils, with Q 10 values typically between 1-2 (Börjesson et al, 2004;Crill, et al, 1994;King and Adamsen, 1992;Roslev et al, 1997;Whalen et al, 1990). Such low values are attributed to slow mass transfer of methane (Dunfield, 2007), although occasionally higher Q 10 values are reported in soils that may have higher gas diffusivity (Christophersen, et al, 2000;MacDonald, et al, 1997) or exposed to methane concentrations greater than 10,000 ppmv (De Visscher, et al, 2001). At temperature extremes, however, i.e., <10 ºC and >40 ºC, methane oxidation is significantly limited in forest and landfill cover soil samples Christophersen, et al, 2000;Czepial, et al, 1996;Whalen and Reeburgh, 1996), likely due to inhibition of mesophilic methanotrophs.…”
Section: Temperaturementioning
confidence: 99%
“…The mineral soil Q10 (Q10 is the value for how many times the oxidation rate increases when temperature is increased 10°C at temperatures below the optimum temperature) of 1.11 for CH 4 uptake indicates that methane uptake is controlled primarily by physical processes (Bowden et al, 1998). Christophersen et al (2000) showed for all the soil investigations, the oxidation rate increased with increasing temperature. Predictably, optimum temperatures were not found in this experimentation.…”
Section: Introductionmentioning
confidence: 97%
“…Effect of soil moisture: Christophersen et al (2000) showed that methane oxidation rate is a function of soil moisture content at different temperatures for the different soils. The optimum soil moisture content was different for each soil and depended on the temperature.…”
Section: Introductionmentioning
confidence: 99%